Can acquire and apply knowledge of entrepreneurship the children? The case of subprogram, my first business: "play to undertake" - Damián Simón, Javier (Nova scientia, 2015)
In Mexico the issue of Entrepreneurship Education (EE) in primary schools is an emerging line in educational research. The main objective of the research was to evaluate the structure and implementation of business plans developed by children under the subprogram My first business: "play to undertake" The research was descriptive and exploratory. Participated 26 students (15 man and 11 woman) of the fifth and sixth grade of Benito Juárez Primary School located in the village of Eden in the municipality of San Juan Bautista Tuxtepec, Oaxaca. Three variables were studied: Business plan, theoretical knowledge of entrepreneurship and entrepreneurial skills of Children. Was applied a questionnaire and a basic document structure of the business plan that provided the Fundación Educación Superior Empresa (FESE), and the data analysis was done using the statistical software SPSS V.19. Generally speaking the results show that the children participants in the subprogram yes acquired and applied knowledge of entrepreneurship because they were able to develop a business plan for your mini company.
¿Pueden los niños adquirir y aplicar conocimientos de emprendimiento? El caso del subprograma, mi primer empresa “emprender jugando”
Keywords: Educación básica; Educación en emprendimiento; Emprendedores; Estrategias de enseñanza